2019
DOI: 10.3934/dcdss.2019142
|View full text |Cite
|
Sign up to set email alerts
|

Shadowing is generic on dendrites

Abstract: We show that shadowing is a generic property for continuous maps on dendrites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…A series of lemmas demonstrates that each T n (X) contains a dense open set in C(X). We proceed in a manner similar to that in [6]. For every f ∈ C(X) and every > 0, we will construct a map g ∈ C(X) with ρ(g, f ) < and find a γ > 0 so that B γ (g) ⊆ B (f ) and B γ (g) ⊆ T n (X).…”
Section: Maps Of Graphitesmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of lemmas demonstrates that each T n (X) contains a dense open set in C(X). We proceed in a manner similar to that in [6]. For every f ∈ C(X) and every > 0, we will construct a map g ∈ C(X) with ρ(g, f ) < and find a γ > 0 so that B γ (g) ⊆ B (f ) and B γ (g) ⊆ T n (X).…”
Section: Maps Of Graphitesmentioning
confidence: 99%
“…Recently, it has been shown that these results extend to the class of continuous maps on dendrites, i.e. locally connected, uniquely arcwise connected continua [6]. This is a class of spaces which includes acyclic graphs and the Julia sets of a large class of quadratic polynomials [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the second section we prove that T S -bi-shadowing property is generic as well as the s-limit shadowing property is dense in the class of all continuous functions defined on any dendrite. Let us mention here that genericity of the (usual) shadowing property on dendrites was recently proved in [6]. In our proof we use a slightly different argument, motivated mainly by the methodology developed for graphs.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in the study of chaotic behaviour on dendrites has been increasing for a few years. For examples, researches focus on shadowing [17], distributional chaos [18], induced map [19], and relations between some chaotic notions [20][21][22][23]. It turns out that most of the results on the interval do not necessarily hold true on dendrites.…”
Section: Introductionmentioning
confidence: 99%